Association of suPAR with progression of cardiovascular calcification and cardiovascular outcomes in peritoneal dialysis patients - Jichao Guan; Haiying Xie; Hongya Wang; Shuting Gao; Shuijuan Shen; Shuangshuang Chen; Shizhu Yuan; Ling Qi; Xiujuan Wu; Shuwen Gong (Renal Failure)
Objective Cardiovascular calcification (CVC) is an important factor influencing cardiovascular outcomes in peritoneal dialysis (PD). We investigated the association of serum soluble urokinase plasminogen activator receptor (suPAR) with CVC progression and cardiovascular outcomes in PD patients.Methods A total of 226 PD patients were recruited in our study. CVC assessments include abdominal aortic calcification (AAC), coronary artery calcification (CAC), and cardiac valvular calcification (ValvC). An increase in calcification score or the appearance of a new ValvC after approximately 24 months were defined as CVC progression. The endpoints were CVC progression, cardiovascular events (CVEs) and cardiovascular mortality.Results Of 226 PD patients, 111 had AAC, 155 had CAC and 26 had ValvC at baseline. At the end of follow-up, 41.1% of patients had AAC progression, 76.7% had CAC progression, and 6.4% had ValvC progression. Elevated serum suPAR was a significant risk factor for AAC progression and CAC progression but was no longer associated with ValvC progression by multivariate logistic regression analysis. The ROC curve showed that serum suPAR had a predictive value for CAC progression (AUC = 0.701). By multivariate Cox regression analysis, higher serum suPAR remained an independent risk factor for CVEs, but no longer an independent risk factor for cardiovascular mortality.Conclusion CVC is prevalent in PD patients. High levels of serum suPAR are associated with AAC progression and CAC progression in PD patients. Serum suPAR can be used as an independent predictor of CVEs in PD patients, but not yet for cardiovascular mortality.